The impact of COVID-19 on sport, physical activity and well-being and its effects on social development (Policy Brief, 2020)
Sport is a major contributor to economic and social development. Its role is well recognized by Governments, including in the Political Declaration of the 2030 Agenda, which reflects on "the contribution sports make to the empowerment of women and of young people, individuals and communities, as well as to health, education and social inclusion objectives."